2016
DOI: 10.1038/onc.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG5 suppresses gastric cancer progression by trapping MTA2 in the cytosol

Abstract: Recently, intriguing new roles for some small nucleolar RNA host genes (SNHGs) in cancer have emerged. In the present study, a panel of SNHGs was profiled to detect aberrantly expressed SNHGs in gastric cancer (GC). The expression of SNHG5 was significantly downregulated in GC and was significantly associated with the formation of a tumor embolus and with the tumor, node and metastasis stage. SNHG5 was a long non-coding RNA, which was a class of non-coding RNA transcripts longer than 200 nucleotides. SNHG5 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 28 publications
6
96
2
Order By: Relevance
“…Cui et al uncovered that upregulated lncRNA SNHG1 contributed to progression of non-small cell lung cancer through inhibition of miR-101-3p and activation of Wnt/β-catenin signaling pathway (25). SNHG5 is anomalously expressed in human gastric cancer and colorectal cancer (16,17). However, its biological function in BC has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cui et al uncovered that upregulated lncRNA SNHG1 contributed to progression of non-small cell lung cancer through inhibition of miR-101-3p and activation of Wnt/β-catenin signaling pathway (25). SNHG5 is anomalously expressed in human gastric cancer and colorectal cancer (16,17). However, its biological function in BC has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al demonstrated that overexpressed SNHG5 significantly represses the progression of gastric cancer (17,26). While, Damas et al uncovered that high level of SNHG5 obviously promotes cell survival in colorectal cancer (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, SNHG5 suppresses GC progression by trapping MTA2 in the cytosol [18], suggesting that SNHGs may also represent novel therapeutic targets for cancer.…”
Section: Introductionmentioning
confidence: 99%